Pathogenesis and clinical significance of atrial fibrillation in myocardial infarction - M. V. Zykov; O. L. Barbarash (Российский кардиологический журнал)
Currently, there is no information in novel clinical guidelines on the importance of active detection of atrial fibrillation (AF) in myocardial infarction (MI), as well as on the management of such patients. The aim of this review was to present actual information about possible risk factors, features of pathogenesis, as well as the prognostic significance of AF in MI. Analysis of the literature has shown that many researchers divide AF into new-onset AF (developed after MI) and chronic AF (existing in history before MI). New-onset AF is common complication in MI according to different studies (from 3 to 28% among all patients with MI), which is associated with death and cardioembolic events. Moreover, in every third patient with MI, AF is asymptomatic, which makes it extremely urgent to develop special algorithms aimed at its active search.